Sino-orbito-cerebral aspergillosis in an immunocompetent patient: a rare case report - Phogat, Jitender; Nada, Manisha; Dahiya, Monika; Solanki, Sneha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Invasive sino-orbito-cerebral aspergillosis is rarely seen in immunocompetent individuals; diagnosis and management of which is still a challenge. We report a case of invasive sino-orbito-cerebral aspergillosis in a 38 year immunocompetent male presenting with mild protrusion of right eye which was associated with no other complaint. His visual acuity was 6/6 in both eyes. There was mild proptosis of right eye of 2 mm on Hertel exophthalmometer with no restriction of the ocular movements. MRI brain, orbit and paranasal sinuses revealed soft tissue swelling in right ethmoid, frontal and sphenoidal air cells and orbit with bony destruction of lamina papyracea with intracranial extension of the mass with destruction of lamina cribrosa. The tissue biopsy was taken from the uncinate process and middle turbinate and sent for histopathological examination which revealed a fibrocollagenous soft tissue which was densely infiltrated by inflammatory cells with presence of large number of foreign body granulomas and filamentous aspergillus fungal hyphae. By radiological and histopathological findings, patient was diagnosed as a case of rhino-orbito-cerebral aspergillosis and given Tb Voriconazole 200 mg BD for 6 months after neurosurgery consultation. His proptosis was revealed at 3 months and repeat MRI showed slightly thickened mucosa of sinuses with no mass lesion seen in the orbit and brain with no evidence of any residual fungal granuloma. Orbital aspergillosis is quite challenging in terms of both diagnosis and treatment. Prolonged antifungal therapy is very effective in controlling infection, if patient is compliant.